Perancangan Sistem Persewaan Ruang Bisnis dengan Metode Prototype - Hardiyanto, Ifan Rifai; Dzikria, Intan (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2023)
Automation helps humans do manual work easily and the information they get is up-to-date. One of the automation implementations is room rental. Room rentals are currently still not widely done online and reach all over Indonesia. Some room providers only use automation for their own space rentals. Ordering and marketing allow only limited automation within the scope of the provider. The purpose of this research is to design a website-based business space rental system using the prototype method. Research shows that business space reservation information systems can manage business space rental data owned by the owner. The system is also capable of automating orders, so that the owner and tenant do not need to communicate directly or go to the rental location. This research can be used as a reference for the industry in designing a space rental information system